Digitization of Villages in Improving Public Services and Technology-Based Archiving in Balikpapan Sub-District - Gunawan Gunawan; Shinta Palupi; Richki Hardi (Jurnal Solusi Masyarakat (JSM), 2023)
Improving public services and efficiency in archiving are important aspects of optimizing governance at the subdistrict level. In an increasingly advanced era of information technology, the digitization of subdistricts offers a promising solution to enhance the quality of public services and the effectiveness of archiving. This paper aims to describe the implementation of subdistrict digitization in enhancing technology-based public services and archiving in the Balikpapan District. This research utilizes a descriptive method by collecting data through literature review, observation, and interviews with relevant parties in the Balikpapan subdistrict. The research findings indicate that subdistrict digitization has successfully provided significant positive impacts in improving public services and archiving efficiency in the Balikpapan District. In terms of public services, subdistrict digitization enables easier and faster access for the community to obtain information and services from the subdistrict government. The utilization of technology-based applications such as public service portals and mobile applications allows the public to submit administrative requests, access essential information, and provide feedback online. This accelerates the service process and reduces excessive bureaucracy. Furthermore, subdistrict digitization also contributes to archiving effectiveness. By adopting a technology-based archiving system, important documents can be stored electronically and well-organized. The use of database technology enables more efficient document search and management, reducing the risk of document loss or damage, and improving the speed of information access. Although there are several challenges in implementing subdistrict digitization, such as limited resources and resistance to change, the efforts made by the Balikpapan subdistrict have proven the positive benefits of adopting this technology. Subdistrict digitization has made a significant contribution to enhancing public services and archiving in the Balikpapan District and can serve as an example for other subdistricts in optimizing technology-based governance.